Penerapan Sanksi Pidana Uang Pengganti untuk Memulihkan Kerugian Negara yang Berasal dari Tindak Pidana Korupsi - Iqbal, Fikri Nur; Sudarto, Sudarto (Neolectura, 2025)
Article 18 paragraph (1) letter b of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 stipulates that replacement money must equal the assets obtained from corruption. However, differences between the law’s explanatory section and the article’s formulation create ambiguity about its intended purpose, leading to dual interpretations in calculating replacement money. This study, using a normative juridical method, finds that imposing replacement money is a legal mechanism to recover stolen state assets. Success is not merely assessed by the amount ordered by the court or the quantity of assets confiscated, seized, or auctioned by prosecutors, but by how much is actually deposited into the state treasury. In Decision No. 1441/Pid.Sus/2019/PN Mks, involving medical malpractice causing serious injury, the court ruled that a subsidiary prison term could not apply because the defendant, Heru Hidayat, was sentenced to life imprisonment—one of two prison types under Article 12(1) of the Criminal Code. Consequently, prosecutors must locate, seize, and auction his assets to fulfill the replacement payment within his lifetime.